PENGEMBANGAN DESAIN PEMBELALAJARAN PECAHAN SENILAI BERBASIS THINK TALK WRITE DENGAN MEDIA LEGO S EBAGAI INOVASI PENINGKAT MOTIVASI BELAJAR - Eka Wahyuni; Anna Rosyadah; Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop a learning design for equivalent fractions using the Think Talk Write (TTW) model integrated with animated video media and LEGO manipulatives to enhance elementary students’ learning motivation. This study employed a Research and Development (R&D) approach adapted from the 4D model, simplified into three stages: define, design, and develop. The product developed consists of an animated instructional video paired with LEGO as concrete manipulatives to support students’ conceptual understanding and active engagement in learning equivalent fractions. Data were collected through expert validation sheets, student response questionnaires, and qualitative feedback from trials. The validation results showed that the media obtained a score of 87% from media experts and 89% from material experts, with an average of 88%, categorized as highly feasible. Field testing conducted with Grade VI students at SD Negeri 1 Saban, Grobogan Regency, produced a student response percentage of 87%, also categorized as highly feasible. Students demonstrated increased motivation, enthusiasm, and active participation when learning through the combination of visual animations and hands-on LEGO activities. The findings indicate that the TTW-based learning design utilizing animated videos and LEGO is valid, practical, and effective in improving students’ motivation to learn mathematics, particularly in understanding equivalent fractions.